Betydningen af detailkædernes egne mærker (private labels) i Norge. - Ingerød, J.; Røtnes, R.; Hansen., H. (Tidsskrift for Landøkonomi, 2024)
Betydningen af detailkædernes egne mærker (private labels) i Norge.